Directed assembly of multiplexed single chirality carbon nanotube devices - Xu, Xinzhao; Mukadam, Zamaan; Amoroso, Giuseppe; Freeley, Mark; Palma, Matteo (Journal of applied physics, 2021)
Herein, we present the fabrication of multiplexed single-walled carbon nanotube (SWCNT) devices, where selected chiralities were separately immobilized on one chip with single-tube precision. Each chirality was subsequently electrically measured individually. Specifically, (6,5) and (7,5) SWCNT species were isolated via aqueous two-phase polymer systems, after which dielectrophoresis was used to precisely control the placement of each chirality, along with a metallic species, separately on prepatterned electrodes on a single chip.